Fatigue assessment of Ti-6Al-4V titanium alloy laser welded joints in absence of filler material by means of full-field techniques (Fracture and Structural Integrity, 2017)
The aim of this research activity was to study the fatigue behavior of laser welded joints of titanium alloy, in which the welding was performed using a laser source and in the absence of filler material, by means of unconventional full field techniques: Digital Image Correlation (DIC), and Infrared Thermography (IRT). The DIC technique allowed evaluating the strain gradients around the welded zone. The IRT technique allowed analyzing the thermal evolution of the welded surface during all the fatigue tests. The fatigue limit estimated using the Thermographic Method corresponds with good approximation to the value obtained from the experimental fatigue tests. The obtained results provided useful information for the development of methods and models to predict the fatigue behavior of welded T-joints in titanium alloy.
Keywords: Fatigue; Welded joints; Marine structures; Digital Image Correlation; Infrared Thermography